P583 The role of parents in predicting sexual health and substance use risk among native american youth. (14th July 2019) - Tingey, Lauren; Chambers, Rachel; Littlepage, Shea; Beach, Anna; Melgar, Laura; Lee, Angie; Rompalo, Anne
Abstract : Background: Native American youth suffer marked disparities in sexual health and substance use. High rates of sexually transmitted infections (STIs), unintended pregnancies and substance abuse are driven by early sexual and substance use initiation and limited access to culturally relevant health education. Parents and extended family members are central to youth decision making in Native communities. Despite this inherent strength, few health education programs are designed to be multigenerational and fail to engage parents and family members in intervention delivery. Methods: Data was collected with N=536 Native youth ages 11–19 participating in an evaluation of a comprehensive sexual health program designed for youth together with their parents or other trusted adult family members, called Respecting the Circle of Life. Baseline data was analyzed to determine how parental monitoring and parent-youth communication predicted sexual and substance use risk prior to intervention implementation. Bivariate and multivariate logistic regression models examined the role of parents in predicting substance use initiation, sexual initiation (vaginal/anal/oral), condom use at last sex, as well as intention to have sex and condom use intention. Results: Final multivariate models indicate parental monitoring significantly predicted: initiation of cigarettes (p=0.02), initiation of marijuana (p=0.001), initiation of vaginal sex (p=0.03), initiation of oral sex (p=0.04), intention to have sex in the next 6 months (p=0.000) and intention to use a condom in the next 6 months (p=0.002). Conclusion: Our findings underscore the powerful role of parents and family in Native American sexual and substance use decision making. Results show Native families can help delay youth's initiation of sex and substances and protect them from the consequences of sexual risk taking. Programs aiming to promote the sexual health of Native youth should incorporate parents and other families in lesson delivery and skill development to maximize impact. Disclosure: No significant relationships.